What model of nutrition can be recommended to people ending their professional sports career? An analysis of the Mediterranean diet and the CRON diet in the context of former athletes - Holowko-Ziólek, J.; Cieszczyk, P.; Bilinski, J.; Basak, G. W.; Stachowska, E. (Nutrients, 2020)
Athletes who retire from their sporting career face an increase in body weight, leading to overweight or obesity. Simultaneously, a significant number of these athletes meet the criteria of metabolic syndrome. The available literature does not offer clearly defined standards of nutrition for the discussed group of people. In this situation, it seems advisable to develop different standards of dietary behavior typical of athletes finishing their sports careers. For this purpose, the study analyzed two types of diets: the Mediterranean diet and the Calorie Restriction with Optimal Nutrition (CRON) diet based on significant calorie restrictions. Both diets seem to meet the requirements of this group of people.